Using training and parental motivational climates to predict performance anxiety at youth football players - Boncu, Alexandru (Technium Social Sciences Journal, 2020)
Drawing on the Self-Determination Theory, the current study examines the relations between two types of anxiety – cognitive and somatic – various variables from a parental and training motivational climates. evaluates whether basic needs from a parental motivational climate has an incremental contribution over training motivational climate in explaining cognitive and somatic anxiety. In a sample of 251 youth football players we found that training competence frustration, training autonomy satisfaction and training relatedness frustration significantly related to cognitive an somatic anxiety dimensions, whereas parental motivational climate variables were not related to the mentioned outcomes. Results indicate that certain training motivational climate factors play a role in anxiety.